Effects of specific versus cross-training on running performance - Foster, C.; Hector, L. L.; Welsh, R.; Schrager, M.; Green, M. A.; Snyder, A. C (European Journal of Applied Physiology, 1995)
The cross-training hypothesis suggests that despite the principle of specificity of training, athletes may improve performance in one mode of exercise by training in another mode. Well-trained (M = 10; F = 20) individuals were placed in an 8-weeks program of enhanced running training or a control group. The enhancement consisted of increasing the work output by 10% through performing either extra running or swimming. The control group followed the basic, non-enhanced running program. There was a significant increase in running velocity at a lactate concentration of 4mM/l in the enhanced-running group but not in the cross-training or control groups. The swimming/cross-training group improved in arm cranking which is associated with that arm-dominant activity. The running groups did not display any arm adaptation. The only changes that were significant in the cross-training group were physiological measures. There was no change in running performance. This study suggests that muscularly dissimilar cross-training may add to improved specific (running) tests but not to the same degree as increased specific training. Only specific training affected running performance. Implication: While cross-training occasionally might show some transfer effects, the size of effects will be less than those which could be attained by increasing specific training by a similar amount. Although cross-training "benefits" are sometimes observed, they usually are in some physiological measures, and rarely in performance. Thus, cross-training, when it works, is a very inefficient method for producing slight performance capacity increases. The emergence of effects in performance is an even rarer event.